Dietary Genistein Alleviates Lipid Metabolism Disorder and Inflammatory Response in Laying Hens With Fatty Liver Syndrome - Lv, Zengpeng; Xing, Kun; Li, Guang; Liu, Dan; Guo, Yuming (Frontiers in Physiology, 2018)
This study was to investigate molecular mechanism of dietary GEN on fatty liver syndrome (FLS) in laying hens. Hens in the control group were fed with a high-energy and low-choline (HELC) diet to establish the FLS model. The livers of FLS hens were friable and swollen from hemorrhage. Hepatocyte steatosis and inflammatory cell infiltration exist around the blood vessels of livers Hens in the low-genistein (LGE) and high-genistein (HGE) groups were fed GEN at 40 mg/kg and 400 mg/kg respectively, as supplements to HELC diet. 40 mg/kg GEN significantly increased the mRNA expression of GnRH in the hypothalamus, the serum level of estrogen, and the laying rate; while 400 mg/kg GEN decreased the expression of GnRH and the laying rate without significant effects on estrogen, suggesting that high-dose GEN adversely affect the reproductive performance. Either high- or low-dose GEN treatment could alleviate metabolic disorders and inflammatory response in FLS hens. GEN significantly decreased the serum levels of ALT, creatinine, triglyceride, total cholesterol and free fatty acids. Accordingly, the levels of TG, long-chain fatty acids, including long-chain saturated fatty acids and monounsaturated fatty acids, as well as the ratio of n-6:n-3 polyunsaturated fatty acids in the liver, were reduced after GEN treatment; while the levels of C22:0, n-3 family fatty acids, C20:3n6 and C20:4n6 were increased. It’s indicated that dietary GEN down-regulated the expression of genes related to fatty acid synthesis (SREBP1c, LXRα, FAS and ACC), and fatty acid transporter (FAT). Furthermore, GEN treatment up-regulated the transcription of genes related to fatty acid β-oxidation (PPARα, PPARδ, ACOT8, ACAD8 and ACADs) in the liver and reduced the expression of PPARγ and AFABP in abdominal fat. dietary GEN alleviated inflammatory cell infiltration in the livers of FLS hens and down-regulated the expression of TNF-α, IL-6 and IL-1β. Moreover, GEN treatment increased the activity of SOD and decreased malondialdehyde in the liver. In conclusion, GEN supplementation in feed inhibited fatty acid synthesis and enhanced β-oxidation in the liver through the PPAR-ACAD/ACOT and PPAR-LXRα-SREBP1c-ACC/FAS/FAT pathways. Dietary GEN alleviated metabolic disorder and inflammation in FLS hens by improving antioxidant capacity and fatty acid profile.